2003
DOI: 10.1007/s00418-003-0539-y
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-Perls and -Turnbull methods supplemented by DAB intensification for nonheme iron histochemistry: demonstration of the superior sensitivity of the methods in the liver, spleen, and stomach of the rat

Abstract: Perfusion-Perls and -Turnbull methods supplemented by the intensification with 3,3'-diaminobenzidine (+ DAB) enabled stronger and more extensive staining of nonheme iron than the Perls + and Turnbull + DAB methods carried out on tissue sections fixed with 10% formalin in 0.9% saline or PBS. The section- and perfusion-Perls + DAB methods are not specific for the demonstration of nonheme ferric iron but also stain nonheme ferrous iron. However, owing to its high sensitivity, the perfusion-Perls + DAB method woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 26 publications
4
57
0
Order By: Relevance
“…To detect ferrous iron, the modified perfusion-Turnbull's technique was used (Meguro et al, 2003). Animals were perfused with a solution containing 1% HCl, 1% potassium ferricyanide, and 4% paraformaldehyde.…”
Section: Animals Cpmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect ferrous iron, the modified perfusion-Turnbull's technique was used (Meguro et al, 2003). Animals were perfused with a solution containing 1% HCl, 1% potassium ferricyanide, and 4% paraformaldehyde.…”
Section: Animals Cpmentioning
confidence: 99%
“…Perl's histochemistry and fAAS detect both the ferrous and ferric forms of iron. To assess whether there was a selective increase in ferrous iron after SCI, we used a variation of the Turnbull's method that allows for the detection of ferrous iron in tissue (Meguro et al, 2003). This analysis revealed that Cp Ϫ/Ϫ mice have more ferrous iron at the lesion site than Cp ϩ/ϩ mice (supplemental Fig.…”
Section: Increased Accumulation Of Iron In the Injured Spinal Cord Of Cpmentioning
confidence: 99%
“…At a rate of 20 ml/min, each animal was perfused with a heparinized 0.005M phosphate buffer containing 0.9% NaCl (0.005 M PBS) (100 ml, pH 7.4) followed by a fixative (prefixative) containing 1% glutaraldehyde (GA) and 4% paraformaldehyde (PA) in 0.005 M PBS (100 ml, pH 7.4). The animals were then perfused with a conventional fixative (1% GA and 4% PA in 0.005 M PBS; 800 ml, pH 7.4), the Perls fixative (800 ml, pH 0.8-1.0) for the perfusion-Perls method, or the Turnbull fixative (800 ml, pH 0.8-1.0) for the perfusion-Turnbull method, as described below (Meguro et al, 2003(Meguro et al, , 2007. Before brain removal, the animals were perfused with saline (0.9% NaCl in distilled water) to flush out the excess Perls or Turnbull fixatives.…”
Section: Animal Treatmentsmentioning
confidence: 99%
“…In this study we took advantage of the highly sensitive perfusionPerls and -Turnbull methods (Yu et al, 2001;Meguro et al, 2003Meguro et al, , 2007 which enabled the production of insoluble nonheme Fe(III) and Fe(II) compounds (Prussian blue and Turnbull blue) in vivo, thereby preventing the inevitable loss of loosely bound nonheme Fe(III) and Fe(II) and the oxidation of Fe(II) during tissue treatments in the traditional Perls and Turnbull staining.…”
Section: Introductionmentioning
confidence: 99%
“…Nonheme Fe (III) and Fe (II) were visualized by the perfusion-Perls and -Turnbull methods, respectively (Meguro et al, 2003(Meguro et al, , 2007. The perfusates for the perfusion-Perls and -Turnbull methods consisted of 4% paraformaldehyde, 1% potassium ferrocyanide (the perfusion-Perls method), or 1% potassium ferricyanide (the perfusion-Turnbull method) in ion-exchanged distilled water, and the desired pH was prepared by adding HCl.…”
Section: The Perfusion-perls and -Turnbull Methods Supplemented By Damentioning
confidence: 99%